Interdecadal changes in at‐sea distribution and abundance of subantarctic seabirds along a latitudinal gradient in the Southern Indian Ocean - CLARA PÉRON; MATTHIEU AUTHIER; CHRISTOPHE BARBRAUD; KARINE DELORD; DOMINIQUE BESSON; HENRI WEIMERSKIRCH (Global Change Biology, 2010)
Long‐term demographic studies have recently shown that global climate change together with increasing direct impacts of human activities, such as fisheries, are affecting the population dynamics of marine top predators. However, the effects of these factors on species distribution and abundance at sea are still poorly understood, particularly in marine ecosystems of the southern hemisphere. Using a unique long‐term data set of at‐sea observations, we tested for interdecadal (1980s vs. 2000s) changes in summer abundance and distribution of 12 species of Albatrosses and Petrels along a 30° latitudinal gradient between tropical and Antarctic waters of the southern Indian Ocean. There were contrasting effects of climate change on subantarctic seabird distribution and abundance at sea. While subtropical waters showed the highest rate of warming, the species that visited this water mass showed the greatest changes in distribution and abundance. The abundance of Wandering Albatrosses ( Diomedea exulans ), White‐chinned Petrels ( Procellaria aequinoctialis ) and Giant Petrels ( Macronectes sp.) declined markedly, whereas the other species showed contrasting trends or did not change. With the exception of the White‐chinned Petrel, these decreases were at least partly related to regional increase in sea surface temperature. The southward shift of Wandering Albatross and Prions ( Pachyptila spp.) distributions could be ascribed to species redistribution or decrease in abundance due to warming of the subtropical waters. Surprisingly, White‐chinned Petrel distribution shifted northward, suggesting more complex mechanisms. This study is the first to document a shift in species range in the Southern Ocean related to climate change and contrasting abundance changes. It suggests that some species might experience more severe impacts from climate change depending on the water masses they visit. As climate changes are predicted to continue in the next decades, understanding species responses to climate change is crucial for conservation management, especially when their conservation status is critical or unknown.